Oral Health Behaviour and its Influence on Oral Health Status and Related Quality of Life among Dental Outpatients - A Cross-Sectional Study - Anusha Divvi; Mohammed Junaid; K.P Indumathi; Seema Ashwin Bhogte; Preetha Elizabeth Chaly; Shivashankar Kengadaran (Wolters Kluwer Medknow Publications, 2024)
Objectives: This study aimed to predict oral health behaviour (OHB) using the theory of planned behaviour (TPB) and determine its influence on oral health status and oral health-related quality of life (OHRQoL) among subjects attending the outpatient department of a tertiary dental hospital in India. Methods: A pre-validated questionnaire was used among 240 randomly selected study subjects to record their demographic details, attitudes (Att), subjective norms (SN) and perceived behaviour control (PBC) with regard to dietary habits (DH), oral hygiene habits (OH) and dental attendance (DA) behaviours. OHRQoL and oral health status of study participants were recorded using Oral Health Impact Profile-14 (OHIP-14) and World Health Organization (WHO) Oral Health Assessment Form (2013), respectively. Multivariate analysis was performed after the necessary bivariate comparisons. Results: Among demographic characteristics, the Socioeconomic status (SES) of the study subjects highly influenced their DH and OH (P < 0.05). DA was largely affected by the age of the study subjects (P < 0.05). While attitude of the study participants greatly affected their DH, PBC largely influenced their OH and DA behaviours (P < 0.05). The OHRQoL and Decayed Missing Filled Teeth (DMFT) levels were strongly influenced by the participants' DA behaviours (P < 0.05). Conclusions: DMFT scores and OHRQoL were highly influenced by DA behaviour besides others. DA instead was influenced by PBC. Hence, there needs to be a conscious shift towards strengthening the skills of the population to promote oral health.